Bingkai Politik Islam Dalam Perspektif Abdul Rashid Moten Suatu Upaya Membentuk Ummah - Lesmana, Hendra (STAI Miftahul Ula Nganjuk, 2017)
Abstract: Islam and Politics are like two currencies in a sense interconnected and inseparable from one another. Speaking of politics in Islam cannot be separated from the figure of the Prophet Muhammad especially related to his hijrah from Makkah to Yathrib (Medina) which is a new chapter in his leadership relay as prophet and apostle as well as a reliable political leader. He has a very strategic role as a highly respected negotiator among Medina society at that time. This is evidenced by the Medina Charter. The birth of the Medina Charter became a point of reference for the arrangement of inter-religious relations in Medina to live peacefully so that it can become a model in building inter-religious and inter-religious relations. This shows a historical fact that the religious-political values propagated by the prophet resulted in a success in bringing human civilization to a holistic-integralistic civilization. At first, Islam propagated by the Prophet Muhammad in the midst of the struggle of Arab society is a representation of the existence of a dialectic between revelation and the accompanying reality in Arab socio-cultural realm so that Islam plays a very urgent role as agent of change for growth and development Even the progress of Arab civilization at that time. In this paper will discuss the thoughts of Abdul Rashid Moten who seeks to build the ummah with the legality of the leader and his capacity as a khilafah raised by the people or peoples consensus.